Development of novel LOXL1 genotyping method and evaluation of LOXL1, APOE and MTHFR polymorphisms in exfoliation syndrome/glaucoma in a Greek population - Chiras,D.; Tzika,K.; Kokotas,H.; Oliveira, S.C.; Grigoriadou,M.; Kastania, A; Dima, K.; Stefaniotou,M.; Aspiotis,M.; Petersen, MB; Kroupis, C.; Kitsos,G. (Mol.Vis., 2013)
PURPOSE: In the Greek population of Epirus, exfoliation syndrome (XFS) and exfoliation glaucoma (XFG) occur at a high prevalence. In this study, we validate a novel lysyl oxidase-like 1 (LOXL1) genotyping method, investigate the previously reported association of LOXL1 with XFS/XFG, and evaluate apolipoprotein E (APOE) and methylenetetrahydrofolate reductase (MTHFR) polymorphisms as genetic risk factors for both conditions in our population. METHODS: Blood samples were collected from 82 patients with XFG, 69 patients with XFS, 52 patients with primary open-angle glaucoma (POAG), and 107 controls. APOE and MTHFR 677C>T genotyping was performed from extracted genomic DNA with established methods. A novel methodology of real-time PCR and melting curve analysis was developed and validated to accurately genotype the LOXL1 G153D and R141L polymorphisms by using two different fluorescent channels of the LightCycler instrument (Roche) examining each SNP separately. RESULTS: No significant differences were observed for the APOE and MTHFR polymorphisms between the patients with XFS, the patients with XFG, and the control subjects. The APOE epsilon2 allele appears to be associated with elevated risk of POAG in our population. Our novel LOXL1 genotyping method was easy to perform, fast, and accurate. A statistically significant association was found for the LOXL1 gene with XFS/XFG in this Greek population. The association of XFS and XFG with G153D appeared to be less powerful in this population (XFS: odds ratio [OR]=2.162, p=0.039, XFG: OR=2.794, p=0.002) compared to other populations, and for R141L, the association was proven only with XFG (OR=3.592, p<0.001). Neither of the two LOXL1 SNPs was significantly associated with POAG. CONCLUSIONS: We confirmed the association between LOXL1 and XFS/XFG, but the APOE and MTHFR polymorphisms are not significant risk factors for the development of XFS/XFG in our population of patients from Epirus (Greece)
DA - 20130520 IS - 1090-0535 (Electronic) IS - 1090-0535 (Linking) LA - eng PT - Journal Article PT - Research Support, Non-U.S. Gov't RN - 0 (Apolipoproteins E) RN - EC 1.4.- (Amino Acid Oxidoreductases) RN - EC 1.4.3.- (LOXL1 protein, human) RN - EC 1.5.1.20 (MTHFR protein, human) RN - EC 1.5.1.20 (Methylenetetrahydrofolate Reductase (NADPH2)) SB - IM
Keywords: Aged; Amino Acid Oxidoreductases; Amino Acid Sequence; Apolipoproteins E; Case-Control Studies; chemistry; Complications; Exfoliation Syndrome; Female; genetics; Genotyping Techniques; Glaucoma,Open-Angle; Greece; Humans; Male; methods; Methylenetetrahydrofolate Reductase (NADPH2); Molecular Sequence Data; Nucleic Acid Denaturation; Polymorphism,Single Nucleotide; Reproducibility of Results